Diagnóstico comunitario de salud del barrio San Agustín sector II, septiembre - diciembre de 2013 - Sarango Valle, Nora Alexandra (2013)
This thesis work has as main goal, to help strengthen the comprehensive care model of the national system of family, community and intercultural health at the University Hospital of Motupe and thus provide statistics and data to the Core Team health - EAIS (Equipment Comprehensive Health Care ) develop local proposals in the health sector , aimed at improving the quality of life of the Neighborhood " San Agustín Sector II " . This study is descriptive as facts and characteristics related to population and environment is detailed , the instrument for data collection was the family record compiled by the MSP to which I add a container primer necessary information all this being annexed for examination and thus obtain the district 's own results . The Barrio “San Agustín Sector II”, is distributed in 22 families and 89 inhabitants. The age group 20 to 64 years together with a prevalence of females in the population. His education is maintained at a basic level. The occupation of the inhabitants is based on agriculture. In the 22 families there consumption of unsafe water, poor sewage and garbage disposal, and hence poverty poor housing conditions, unemployment or informal employment of the household head and overcrowding. Regarding the epidemiological profile Hypertension is prevalent in chronic degenerative population followed by the Diabetes disease and a school was also identified with intellectual disabilities. Research bibliography and appendices which involves the development of it is supported. Keywords: Community health diagnosis Neighborhood “San Agustín Sector II” and its results.